MACROECONOMICDETERMINANTS OF FOREIGNINDEBTEDNESS: EVIDENCE FROM PAKISTAN - Minhaj-ud-Din,; Khan, Muhammad; Fatima, Arooj; Bashir, Noman; Hussain, Arif; Imtiaz, Shoaib (The journal of contemporary issues in business and government, 2021)
The intention of conducting this research is to inspect the key macroeconomic determinants of foreign indebtedness in Pakistan. ARDL bound test is applied to annual dataranging from 1976-2018.This paper finds that debt service payment, military spending, and trade openness provoke furtherexternal borrowing, whereas growth in economic activity, depreciation of currency and capital inflow help in curtailing the overseas borrowing of our economy. The findings of this study also highlight the role of government revenue and inflation in reducing the debt burden liability. This study recommends that policy making departments should focus on relaxing the trade barriers, enhancing the overall productivity and competitiveness of the markets, stabilizing the exchange rate and designing an optimal level of military budget as all of them are contributing towards reducing the external financial liabilities.Appropriate use of foreign reserves, creating attractive environment for investment and utilization of funds in revenue-oriented projects are also necessary for combating with the issue of foreign indebtedness. Taken together, the assurance of these recommendations will help in meeting the government's financial needs and curtailing the demand for accumulation of external debt.